The Effect of Separation on Poverty and Employment - Barbara Broadway; Guyonne Kalb (Institute of Labor Economics (IZA), 2025)
Using 2001–2021 HILDA survey data, this paper estimates how separation or divorce affects poverty and employment trajectories over five years after the event. A difference-in-differences approach compares separated individuals with couples who stayed together, accounting for recent and long-term labour market history prior to separation. Women with preschool children face a 19.9 percentage point higher poverty risk in the first year, which fades within three years. Women with older or no children experience smaller but longer-lasting poverty increases. Pre-separation employment strongly moderates effects: non-employed women face much higher poverty risks than employed women who have similar poverty risks to men. Men's poverty impacts are smaller and shorter-lived. Separation barely changes women's employment but slightly reduces men's employment, especially those with preschool children.
Keywords: I32; J12; J16; 330; relationship breakdown; poverty; economic autonomy